The challenges of the landing obligation in EU fisheries. (August 2017) - Catchpole, Thomas L.; Ribeiro-Santos, Ana; Mangi, Stephen C.; Hedley, Christopher; Gray, Tim S.
Abstract: A feasibility study was conducted on the impacts of the new Common Fisheries Policy (CFP) rules requiring catches in regulated fisheries to be landed and counted against quotas of each Member State - the landing obligation (LO), and that catch of species subject to the LO below a minimum conservation reference size (MCRS) be restricted to purposes other than direct human consumption. The aim was to estimate the level of discarded fish likely to be covered by the new rules, the impact of the rules on EU fisheries and the regulatory challenges and responses to them. Data from EU's Scientific, Technical and Economic Committee on Fisheries (STECF) database were analysed to estimate the volume of unwanted catches produced by EU fisheries. Views were sought from policy officials and fisheries scientists through a questionnaire on the implications of the LO and the control of fisheries across Member States, and the potential adjustments that might be needed. Findings show that 11% (44, 000 t) of the total catches of EU countries from which data were available are of fish under MCRS. The species with the highest volume of undersized discards associated with the lowest quota, which would potentially restrict the fishing opportunities for other quota species (i.e. choke species), are plaice and haddock with 18, 000 and 14, 000 t of undersized fish respectively, followed by whiting and cod with 5000 and 6000 t of undersized fish respectively. Discards data shows that the Netherlands, United Kingdom, France and Belgium will be most affected by landings for non-human markets. Findings also show that existing infrastructure at landing ports in all Member States is limited because there are currently limited facilities in place to handle animal by-products produced by the catching sector. Policy officials maintained that while they could support the fishing industry through funding programmes, it is the responsibility of fishers to ensure they have the right infrastructure to handle unwanted catches. The expectation is that the LO combined with the restriction to non-human consumption purposes will encourage fishers to internalise the costs of catching unwanted fish and motivate them to avoid unwanted catch. This will be realised if sufficient flexibility is given to fishers to find their own solutions to reducing unwanted catches. It is concluded that gear technology measures exist to enable the regulated fisheries to increase gear selectivity. Highlights: Assessment of impact of landing obligation and restrictions of catch below minimum conservation reference size. 11% of catch from EU countries from which data are available are of fish under MCRS. Potential choke species include plaice, haddock, whiting and cod. Existing landing port infrastructure to deal with discards in all Member States is limited. Sufficient flexibility should be given to fishers to find their own solutions to reducing unwanted catches.